Efeitos da financeirização sobre o investimento produtivo em firmas não-financeiras de commodities: evidências para o Brasil no período de 2007 a 2022 - Diego Rocha Rebelo (2023)
Financialization and its relationship with the demand for fixed capital investments of non-financial firms have been a recurring theme in the global economic research agenda in recent years. Being a relatively new phenomenon, whose roots in its most current sense are grounded in the rise of neoliberalism and the productive crises of the 1970s-80s in the United States of America and Europe, there are still few studies that have devoted themselves to studying the phenomenon in Brazil, particularly in more recent years, and considering specific categories of firms, such as commodity producers. According to this literature, financialization refers to the engagement of non-financial businesses with financial markets. Furthermore, it can be understood as an accumulation pattern in which profits stem from financial channels rather than originating from the production and trade of goods and commodities. Given that Brazil is a major producer and exporter of commodities, this work aims to investigate the occurrence of financialization and its effects on the demand for fixed capital investments of 88 publicly traded Brazilian non-financial commodity firms between the years 2007 and 2022. In this regard, the phenomenon is examined through two channels of financialization traditionally studied in the literature: firm financial investments and shareholder value maximization. To this end, the study involves the application of dynamic panel data methodology using the GMM-Difference and GMM-System estimation strategies. The findings reveal the occurrence of financialization through the shareholder value maximization channel, which demonstrated a negative contribution to the fixed capital investments of the analyzed firms during the study period. However, for the firm financial investments channel, an atypical result was observed, especially considering the size of the firms included in the sample, indicating a positive contribution to fixed capital investments, raising the hypothesis that this channel may behave differently in commodity firms, but this requires further studies to confirm it.